Opportunistic records reveal Mediterranean reptiles' scale‐dependent responses to anthropogenic land use. Issue 3 (4th December 2018) - De Solan, Thomas; Renner, Ian; Cheylan, Marc; Geniez, Philippe; Barnagaud, Jean‐Yves
Abstract : Although classified among the greatest threats to the world's biodiversity, the effects of land use and their scale dependency are left unexplored in many taxonomic groups. Reptiles are among the most data‐deficient vertebrates in this respect, although their ecological traits make them highly sensitive to habitat modifications. We tested whether land use gradients shape the distributions of Mediterranean reptiles at regional and local scales, and whether species' ecological traits and phylogeny explain these patterns. Reptiles are generally rare and hard to survey through standardized protocols. We overcame these obstacles by modeling an original data set of 18164 opportunistic occurrence records for 14 reptile species with spatially‐explicit point process models incorporating known sources of sampling heterogeneity and spatially autocorrelated error. At a regional scale, reptiles favored open habitats and tended to avoid urban areas. At a local scale, the persistence of open habitats did better than forest resulting from land abandonment in maintaining reptiles within a heavily anthropogenic matrix. Contrary to our expectations, the absence of any clear trait or phylogenetic signals suggests that these responses are mediated by a complex interplay between species' ecology and regional biogeographic history. These results demonstrate that reptile responses to land use are scale‐dependent and locally exacerbated when anthropogenic pressure is high. We further show that land abandonment is insufficient to preserve reptiles in the face of anthropogenic pressures unless patches of suitable habitat are effectively maintained. Eventually, our study further illustrates the effectiveness of volunteer‐based opportunistic sampling in testing hypotheses on the determinants of rare species' distributions.